Phenomenological Study : No Mobile Phone Phobia (Nomophobia) at Junior High School’s Students - Sri Hindriyastuti; Herlina Wietya Anggraeni; Gardha Rias Arsy; Vera Fitriana (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: One form of current technological development is the smartphone. Initially, smartphones were only used by adults, but in this modern era, many teenagers use smartphones. One of the positive impacts of smartphones for school-age youth is being able to find learning materials easily and being able to communicate remotely with teachers, while the excessive use of smartphones has a negative impact, both physically and psychologically. Another bad impact is nomophobia. Nomophobia or commonly known by the abbreviation